Response of thigh muscle cross-sectional area to 21-days of bed rest with exercise and nutrition countermeasures - Liphardt, Anna Maria; Bolte, Vera; Eckstein, Felix; Wirth, Wolfgang; Brüggemann, Gert Peter; Niehoff, Anja (Translational Sports Medicine, 2020)
Human skeletal muscle atrophies in response to reduced mechanical loading. The study aimed to define the muscle-specific anatomical cross-sectional area (ACSA) location that is most sensitive to immobilization and to investigate the effectiveness of resistive vibration exercise, alone, or combined with protein supplementation, against muscle atrophy. Eleven individuals (35.2 ± 8.1 years, 22.6 ± 1.7 kg/m2) were analysed in trial 1, and eight subjects (37.1 ± 6.7 years, 23.0 ± 1.8 kg/m2) in trial 2. Subject received control (CON), vibration training (RVE) (25 minutes à 2 sessions/wk), or RVE + nutrition (NEX) interventions (whey protein + potassium/bicarbonate). Magnetic resonance images (MRI) of both thighs were acquired before, during, and 6 days after 21-days of bed rest to determine ACSAs in regions of interest (ROI) between 10% and 90% of the proximal end of the M. rectus femoris tendon and the end of the femoral neck. Muscle atrophy was highest at the location of their greatest ACSA. ACSA of all muscles at 70% of ROI was reduced after bed rest during CON (range −4.7% to −14.8%) and remained reduced after 6 days of recovery for the majority of muscles (range −3.4% to −8.3%) except for M. vastus lateralis, M. vastus medialis, M. sartorius, and knee flexors. Applied countermeasures had no effect. In conclusion, thigh muscle atrophy can be monitored using ACSA and RVE or NEX was not sufficient to prevent muscle atrophy during 21-days bed rest.
CRIS-Team Scopus Importer:2024-12-16
Keywords: anatomical cross-sectional area; immobilization; muscle atrophy; nutritional countermeasure; space flight; whole body vibration training